3-(2/9b)=(2/3b)-7

Simple and best practice solution for 3-(2/9b)=(2/3b)-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3-(2/9b)=(2/3b)-7 equation:


b in (-oo:+oo)

3-((2/9)*b) = (2/3)*b-7 // - (2/3)*b-7

3-((2/9)*b)-((2/3)*b)+7 = 0

(-2/9)*b+(-2/3)*b+3+7 = 0

10-8/9*b = 0 // - 10

-8/9*b = -10 // : -8/9

b = -10/(-8/9)

b = 45/4

b = 45/4

See similar equations:

| .75c=11.25 | | (2)2/3e=1/18 | | 4x-12=6x-12-2x | | x+4+x+5+x+2=x+3+x+1+x+3+x+1 | | 25x+16-36x=46+12 | | 1.1p=5.28 | | 8*6x=10*9x | | 2x+4[2-(5x-3)]=0 | | 2(0.5x+x-10)=2(x-6+0.25x) | | y=2.9 | | (-2u^2+5u+3)-(-9u^2-7u+3)= | | x^4+5x-2=0 | | p+(-3p+6)=4a(-5p+3)-10p | | 9=12x-6-7x | | n^2-2n=11 | | x^(2/3)=9 | | Y=sin(16x) | | x+2x=45600 | | F(x)=3/4x-5 | | ln(x+3)+ln(x+5)=0 | | 4m+4m-8m+m=9 | | .3a=14 | | 5-3(2X-4)=29 | | 2y+13= | | (1/2)(sqr3/2) | | 8x^4+16x^3-12x^2+4x= | | D=10+7 | | 2(sqr3/2) | | 8w^2=32 | | 14h-3h+-17h=18 | | 5m^2=125 | | -7(1-8a)+5a=-7+5a |

Equations solver categories